?GENOTYPE-ENVIRONMENT INTERACTION AND STABILITY PARAMETERS FOR PADDY YIELD (Biological Sciences - PJSIR, 1999)
Six rice genotypes were evaluated for paddy yield across five locations during 1993. The differences among rice genotypes and locations were highly significant. Genotype x location interaction was also highly significant. Stability analysis showed that rice genotypes, Super Basmati (4048) and Basmati 385, were stable for paddy yield because of mean yield greater than grand mean yield, regression coefficient near unity and small deviations from regression (S2d). S2d was significant for all genotypes except for 4048 and Basmati 385. The rice line 4439 with maximum mean paddy yield (4926 kg ha') across locations, was found to be suitable in Nuclear Institute for Agriculture and Biology, Faisalabad (NIAB) and Gujranwala environments ..